Efeitos do treinamento físico combinado e da suplementação com probiótico na rigidez arterial em ratos tratados com dexametasona - Paula, Vinicius Ferreira de (2023)
Arterial stiffness is recognized as a predictive marker of future cardiovascular diseases and can be assessed by pulse wave velocity (PWV). On the other hand, combined training (CT) has emerged as a promising non-pharmacological strategy in preventing dexamethasone (DEX)-induced arterial stiffness. Moreover, DEX is known to cause intestinal dysbiosis. Therefore, the aim of this study was to investigate the impact of inflammation resulting from intestinal dysbiosis on arterial stiffness and how CT and probiotic supplementation can prevent DEX-induced arterial stiffness. The hypothesis of this work is that alterations in the intestinal microbiota are involved in DEX-induced arterial stiffness and that CT, with or without probiotic supplementation, attenuates arterial stiffness induced by chronic DEX treatment by reducing collagen formation in the aorta. 143 Wistar rats (200-250g) were divided into 8 groups: sedentary control (SC, n=18), sedentary probiotic (SP, n=19), sedentary DEX (SD, n=22), sedentary DEX probiotic (SPD, n=20), trained control (TC, n=10), trained probiotic (TP, n=14), trained DEX (TD, n=15), and trained probiotic DEX (TPD, n=13). The rats were supplemented with probiotic (Yakult®, 2ml/65g via gavage) or water and subjected to CT (treadmill and ladder, on alternate days, at 60% of maximum physical capacity) for 74 days or remained sedentary. During the last 14 days, the rats were treated with DEX (50µg/kg per day, s.c.) or saline concomitant with the other interventions. PWV, blood pressure (BP), spectral analysis, densitometric quantification of extracellular matrix proteins in the aorta, as well as plasma inflammatory biomarkers, were evaluated. The results are presented as mean ± standard error of the mean (SEM). Analysis of variance (ANOVA) was used, and samples showing significant differences were analyzed by Tukey's post hoc test, with (p< 0.05) considered significant. DEX caused an increase in PWV (+68%) and LF (+126%) for SD vs SC, while supplementation and/or CT prevented this increase (- 39%, -33%, -38% and -44%, -88%, -64%) for SPD, TD, and TPD vs SD for PWV and LF, respectively. DEX increased the expression of COL-3 (+59%), TGF-β1 (+59%), TGFR2B (+103%), p-SMAD2/3/SMAD2/3 (+41%), and both probiotic and CT prevented the increase. Regarding quantification of proteins in the distal colon, DEX caused a decrease in claudin-1 (-53%) and an increase in occludin (+161%), and supplementation and/or CT prevented this response for claudin-1 (SP = +84% and TPD +16% vs SC and SD, respectively). Finally, no significant differences were observed in inflammatory biomarkers. The present study suggests that the intestinal microbiota plays an important role in the increased arterial stiffness induced by DEX through prevention of sympathetic activity rather than inflammation. Furthermore, CT was shown to be as effective as probiotic supplementation in attenuating the increase in PWV.